Comprehensive Study of Emergency Preparedness, Healthcare Infrastructure, and Workforce Capacity in General Hospitals - Alghammas, Mohammed Abdulrahman A; Alharbi, Faisal Hamad; Alenzi, Muteb Onayzan Mahal; Al-Rashidi, Saad Sahman; Alkhars, Ali Abdulmohsen J.; ALharbi, Omar Saleh Mohammed; Alrashdi, Sultan Muidh Rwaished; Al-Fahid, Abdulaziz Nayef Saleh; Alshammri, Munifah zayaid Ashawi; Alharbi, Omar Mohammed (Journal of Ecohumanism, 2024)
General hospital emergency preparedness is an essential element of enduring and healthy healthcare systems, making a direct impact in emergencies like pandemics, natural catastrophes, and instances of mass casualties. This paper investigates the cross-sectional relationship between emergency readiness, health facility development, and workforce readiness in general hospitals. Using both qualitative and quantitative methods, the study provides exploratory, descriptive, and conclusion case analysis, questionnaires, and literature reviews to compare practice and research findings. Certainly, future research should stress the importance of constructing efficient communication infrastructures, managing healthcare personnel appropriately, and providing training more frequently. Recommendations made include resource optimization to support the structural readiness of hospitals, collaborative practice, and the adoption of new technologies.